EFFECTS OF CERVICAL STABILIZATION EXERCISES ON NECK PROPRIOCEPTION IN PATIENTS WITH CERVICOGENIC HEADACHE - DEEPIKA SHARMA,; SIDDHARTHA SEN,; AMIT DHAWAN, (International Journal of Pharma and Bio Sciences, 2014)
Cervicogenic headache is gaining prevalence in young adults along with proprioception deficit in the cervical region. Methodology: In this study, 30 participants who met the diagnostic criteria for Cervicogenic headache were randomized into two groups: experimental group and control group. The control group was given stretching exercises. The experimental group in addition to stretching performed cervical stabilization exercises. The intervention was followed 3 times a week for 4 weeks. Prior to and after the programme, Headache disability index and neck proprioception were evaluated. Both the groups had significantly reducedHeadache disability index scores and neck proprioception error at the end of 4th week (p<0.05). Headache disability index scores and neck proprioception error improved more in the experimental group.Conclusion: Cervical stabilization exercises along with stretching are more effective in improving neck proprioception and Headache disability index than stretching alone.